2010
DOI: 10.1186/1756-0500-3-267
|View full text |Cite
|
Sign up to set email alerts
|

Structural equation modeling in medical research: a primer

Abstract: BackgroundStructural equation modeling (SEM) is a set of statistical techniques used to measure and analyze the relationships of observed and latent variables. Similar but more powerful than regression analyses, it examines linear causal relationships among variables, while simultaneously accounting for measurement error. The purpose of the present paper is to explicate SEM to medical and health sciences researchers and exemplify their application.FindingsTo facilitate its use we provide a series of steps for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
212
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(245 citation statements)
references
References 29 publications
1
212
0
7
Order By: Relevance
“…The goal of predictive analysis is to maximize model fit and a decision on whether to retain a particular covariate is based on statistical considerations (Bellazzi and Zupan 2008). By contrast, in an explanatory (hypothesis testing) analysis, inclusion and exclusion of control variables (confounders, mediators or effect modifiers) are driven, at least in part, by a priori reasoning (Concato et al 1993;Hernan et al 2002;Beran and Violato 2010).…”
Section: Data Analysis and Reporting Of Resultsmentioning
confidence: 99%
“…The goal of predictive analysis is to maximize model fit and a decision on whether to retain a particular covariate is based on statistical considerations (Bellazzi and Zupan 2008). By contrast, in an explanatory (hypothesis testing) analysis, inclusion and exclusion of control variables (confounders, mediators or effect modifiers) are driven, at least in part, by a priori reasoning (Concato et al 1993;Hernan et al 2002;Beran and Violato 2010).…”
Section: Data Analysis and Reporting Of Resultsmentioning
confidence: 99%
“…The model-generated covariance structure can be as complicated as the conceptual model being tested, and has the scope of including latent variables via the observed variables in the data. One of the greatest advantages of SEM is perhaps its ability to manage measurement error, which is one of the greatest limitations of most studies (Beran and Violato 2010). Hence, SEM is a powerful multivariate tool that encompasses the techniques of multiple regression as well as factor models.…”
Section: Structural Equations Modellingmentioning
confidence: 99%
“…Buncher et al (1991) indicated that the methods of SEM are useful in studying environmental issues as this technique is well-suited to studies involving measurements at successive time points with complex interrelationships (Kelloway 1995). SEM has since been applied in disciplines, such as medicine (Stephenson et al 2006), organisational behaviour (Das et al 2011), education (Teo and Khine 2009) and evolutionary biology (Bruce et al 2003), to name a few, but has not been used extensively in epidemiology (Beran and Violato 2010). SEM allows one to move away from individual level modelling, as in regular regression models, towards modelling the overall covariance structure prevalent among the variables and captured via individual observations.…”
Section: Structural Equations Modellingmentioning
confidence: 99%
“…El ajuste del modelo fue examinado con: 1) la prueba χ 2 de bondad de ajuste (un valor p no significativo es deseable); 2) el índice de ajuste comparativo y el índice de ajuste no normalizado de Bentler-Bonet (CFI y BBNNFI por sus siglas en inglés; valores mayores a 0.90 son deseables) (20) ; y 3) la raíz cuadrada del cuadrado medio del error de aproximación (RMSEA por sus siglas en inglés; valores menores a 0.05 indican un excelente ajuste y entre (0.05-0.08) son aceptables (21) ). En la elección del modelo más parsimonioso se empleó el estadístico del multiplicador de Lagrange.…”
Section: Métodosunclassified